2003
DOI: 10.1007/s00204-003-0454-y
|View full text |Cite
|
Sign up to set email alerts
|

A role of aryl hydrocarbon receptor in the antiandrogenic effects of polycyclic aromatic hydrocarbons in LNCaP human prostate carcinoma cells

Abstract: The role of aryl hydrocarbon receptor (AhR) on the antiandrogenic effects of polycyclic aromatic hydrocarbons (PAHs) was studied in LNCaP cells. The PAHs used in this study were chrysene (Chr), benzo[ k]fluoranthene (BkF), benzo[ a]pyrene (BaP), anthracene (Ant) and pyrene (Pyr). Chr, BkF and BaP acted as AhR agonists in LNCaP cells, while Ant and Pyr did not. The antiandrogenic effects of the PAHs were evaluated on the basis of regulation of prostate-specific antigen (PSA) mRNA and protein levels by 5alpha-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
59
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(62 citation statements)
references
References 46 publications
3
59
0
Order By: Relevance
“…This observation is significant because it suggests that the reduced sperm motility observed among treated rats is secondary to reduced epididymal exposure to physiological concentrations of androgens. According to Vinggaard et al (2000), Kizu et al (2003), and Charles et al (2005), PAHs including BaP and/or their metabolites perturb the androgen-dependent processes in target tissues by acting as antiandrogens. Benzo(a)pyrene may interrupt epididymal function by competing for androgen receptors in this organ (Mahony and Hodgen, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…This observation is significant because it suggests that the reduced sperm motility observed among treated rats is secondary to reduced epididymal exposure to physiological concentrations of androgens. According to Vinggaard et al (2000), Kizu et al (2003), and Charles et al (2005), PAHs including BaP and/or their metabolites perturb the androgen-dependent processes in target tissues by acting as antiandrogens. Benzo(a)pyrene may interrupt epididymal function by competing for androgen receptors in this organ (Mahony and Hodgen, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…PAHs and their metabolites may be hormonally active [48,49]. PAHs can bind and stimulate the acryl hydrocarbon receptor (AhR) which, in turn, may induce increased metabolism of PAHs to biologically active products that can interact with DNA and promote cancer, or other adverse outcomes [50].…”
Section: Ijomeh 2013;26(5) 797mentioning
confidence: 99%
“…Typical AhR agonists, such as 2,3,7,8-TCDD and certain PAHs, are found to elicit antiandrogenic effects through AhR-mediated mechanisms without binding to AR. [16][17][18] We demonstrated that diesel exhaust particle extracts exhibited antiandrogenic effects in PC3/AR cells, and that the major part of the antiandrogenic effects are caused by constituents with AhR agonist activity. 22 Further, the importance of the AhR agonist on male reproductive-system functions has been suggested by in vivo studies.…”
Section: Resultsmentioning
confidence: 92%
“…[16][17][18] We demonstrated that diesel exhaust particle extracts exhibited antiandrogenic effects in PC3/AR cells, and that the major part of the antiandrogenic effects are caused by constituents with AhR agonist activity. 22 Further, the importance of the AhR agonist on male reproductive-system functions has been suggested by in vivo studies. It has been shown that 2,3,7,8-TCDD impairs male reproductive functions in animal models 4 and that TCDD exerts its adverse effects without affecting the circulatory androgen 56…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation